Amazement of Complex Integration - Paeyndah, Azizullah (Journal for Research in Applied Sciences and Biotechnology, 2022)
In this article, we discuss the facts and wonders of complex integrations. We describe the differences between integrations and complex integrations. These differences show the wonders of complex integrations.